Biosimilar recombinant follitropin alfa preparations versus the reference product (Gonal-F®) in couples undergoing assisted reproductive technology treatment: a systematic review and meta-analysis - Su Jen Chua; Ben W. Mol; Salvatore Longobardi; Raoul Orvieto; Christos A. Venetis; Monica Lispi; Ashleigh Storr; Thomas D'Hooghe (BMC, 2021)
Abstract Background Live birth has increasingly been identified as the standard clinical approach to measure the success of medically assisted reproduction (MAR). However, previous analyses comparing biosimilar preparations of follitropin alfa versus the reference product (GONAL-f®, Merck KGaA, Darmstadt, Germany or GONAL-f® RFF; EMD Serono, Inc., Rockland, MA), have had insufficient power to detect differences in clinically meaningful outcomes such as live birth. Methods Medline, Embase, the Cochrane Library, Web of Science and clinical trial registries were searched for randomised controlled trials (RCTs) and conference abstracts comparing biosimilar follitropin alfa versus the reference product in controlled ovarian stimulation (COS) cycles published before 31 October 2020. Only studies in humans and publications in English were included. Retrieved studies were screened independently by two authors based on titles and abstracts, and then by full text. Inclusion criteria: RCTs comparing follitropin alfa biosimilar preparations with the reference product in infertile patients of any age, with any type of infertility for any duration, undergoing COS for the purposes of MAR treatment (including frozen cycles). The primary outcome was live birth. Combined data for biosimilar preparations were analysed using a fixed-effects model. Results From 292 unique records identified, 17 studies were included in the systematic review, representing five unique RCTs that were included in the meta-analysis. Rates of live birth (RR = 0.83, 95% CI 0.71, 0.97; 4 RCTs, n = 1881, I2 = 0%), clinical pregnancy (RR = 0.82, 95% CI 0.72, 0.94; 4 RCTs, n = 2222, I2 = 0%) and ongoing pregnancy (RR = 0.81, 95% CI 0.68, 0.96; 4 RCTs, n = 1232, I2 = 0%) were significantly lower with biosimilar preparations versus the reference product. Rates of cumulative live birth and cumulative clinical pregnancy were also significantly lower with biosimilars versus the reference product. There was high risk of publication bias. Conclusions This meta-analysis included data from RCTs evaluating the efficacy and safety of the biosimilar follitropin alfa preparations and demonstrated lower probability of live birth and pregnancy (ongoing and clinical) in couples treated with biosimilar preparations compared with the reference product. This study provides more insight into the differences between biosimilar r-hFSH preparations and the reference product than previously reported. Trial registration Registration number: CRD42019121992 .